CORRELATION OF MISSING OUT (FOMO), ANXIETY AND AGGRESSION OF YOUNG ADULTS - Kacker, Priyanka; Saurav, Saket (International Journal of Research -GRANTHAALAYAH, 2020)
Social media now has become integral part of human race. It not only helps in knowing about the opportunity one has online but also offline. On the upside, these resources provide multiple opportunities for interaction; on the downside, they often give us more than required amount of options that often lead to confusion and distress and have practical restrictions. The use of social media is so prevalent that it is leading society towards cyber distress. Thus, this study attempts to study the correlation between FoMo, Social Media Addiction, Personal Relationship, Aggression Factor one, two, three and four and Anxiety. A total of 600 sample population was selected for this purpose and a total of 60 sample (30- Neutral group and 30- High score Group) for study of brain electrical wave pattern. The tool used in this study was FoMo and Social Media Addiction Questionnaire, Personal Relationship Questionnaire, Buss and Perry aggression scale and Zung Anxiety scale. The result reveals that there is a positive significant correlation between FoMo, Social Media Addiction and Psychological Factors at (p<0.001 and p<0.005).